Digital Content Marketing in Communicating Green Initiatives of Sustainable B2B Companies in Sweden - Nguyen, Pham Thuy Trang (2022)
Green marketing has increasingly gained the attention of corporate decision-makers and global firms. As several motivations lead companies to go "green," understanding what and how to communicate with the target audience to excel in the race of business performance is essential. Fortunately, digitalization has proposed new possibilities for more effective message delivery, for instance, digital content marketing on social media. However, the green marketing literature has neglected the use of digital content marketing to strategically support and communicate green initiatives. Thus, the present study investigates how digital content marketing could be applied in the green marketing of B2B sustainable companies. Specifically, it aims to describe green marketing and first link this term with digital content marketing through five components of green marketing mix: Distribution/Market, Price, Product, Promotion, and Production. The research goals were accomplished using qualitative research of 165 social posts and reporting on a content analysis of the three most sustainable brands in Sweden in two industries: FMCG and Energy. Three case companies are Lantmännen (#1), Vattenfall (#4), and Orkla Group (#6). The empirical findings reveal that the B2B firms differ in ways of distributing content and preferences of content types and formats. However, it proved LinkedIn as the preferred channel to push green digital content, with the primary focus on products, innovation, and technology. Combinations of text, image, video, and links were widespread in all case companies. To confirm the alignment between content and companies' sustainable development goals (SDGs), the study finds that the more content mentioned about SDGs, the more it impacts customers in terms of interaction. Thus, it has been discovered that goal-oriented digital content marketing is essential to tie up the connection between firms' goals and green marketing communication goals. In the end, this thesis will spark more investigation and serve as a resource for those concerned with these topics.